Development of E-Student Worksheet Based on STEM Approach with PBL Model to Facilitate Critical Thinking Skills on Momentum and Impulse Material - Febriyanti Febriyanti; Ratnawulan Ratnawulan; Hidayati Hidayati; Emiliannur Emiliannur (Jurnal Penelitian Pembelajaran Fisika, 2026)
This research is motivated by the low critical thinking skills of students in physics learning and the unavailability of digital teaching materials capable of supporting the implementation of the Independent Curriculum. This study aims to develop and analyze the validity of Electronic Student Worksheets based on the Science, Technology, Engineering, and Mathematics (STEM) approach with the Problem Based Learning (PBL) model on momentum and impulse material to facilitate critical thinking skills of high school students. This study uses the Research and Development (R&D) method with the Four-D (4D) model limited to the define, design, and develop stages. Product validity was assessed by three expert validators using validation instruments analyzed with the Aiken's V index. The results showed that the developed E-Student Worksheet obtained an average validity value of 0.87 with a very valid category. All assessment aspects, namely material substance, visual communication display, E-Student Worksheet components, software utilization, STEM approach, PBL model, and critical thinking skills, were in the very valid category. Based on these results, the STEM-based E-Student Worksheet with the PBL model is declared suitable for use as a digital teaching material to support physics learning on momentum and impulse materials and has the potential to facilitate the development of students' critical thinking skills.